Structural Changes of Amyloid Beta in Hippocampus of Rats Exposed to Ozone: A Raman Spectroscopy Study - Rivas-Arancibia, Selva; Rodríguez-Martínez, Erika; Badillo-Ramírez, Isidro; López-González, Ulises; Saniger, José M. (Frontiers in Molecular Neuroscience, 2017)
The aim of this work was to study the effect of oxidative stress on the structural changes of the secondary peptide structure of amyloid beta 1–42 (Aβ 1–42), in the dentate gyrus of hippocampus of rats exposed to low doses of ozone. The animals were exposed to ozone-free air (control group) and 0.25 ppm ozone during 7, 15, 30, 60, and 90 days, respectively. The samples were studied by: 1) Raman spectroscopy to detect the global conformational changes in peptides with α-helix and β-sheet secondary structure, following the deconvolution profile of the amide I band; and 2) immunohistochemistry against Aβ 1–42. The results of the deconvolutions of the amide I band indicate that, ozone exposure causes a progressively decrease in the abundance percentage of α-helix secondary structure. Furthermore, the β-sheet secondary structure increases its abundance percentage. After 60 days of ozone exposure, the β-sheet band is identified in a similar wavenumber of the Aβ 1–42 peptide standard. Immunohistochemistry assays show an increase of Aβ 1–42 immunoreactivity, coinciding with the conformational changes observed in the Raman spectroscopy of Aβ 1–42 at 60 and 90 days. In conclusion, oxidative stress produces changes in the folding process of amyloid beta peptide structure in the dentate gyrus, leading to its conformational change in a final β-sheet structure. This is associated to an increase in Aβ 1–42 expression, similar to the one that happens in the brain of Alzheimer’s Disease patients.